Software engineering for resilient systems : 11th International Workshop, SERENE 2019, Naples, Italy, September 17, 2019, Proceedings /: 11th International Workshop, SERENE 2019, Naples, Italy, September 17, 2019, Proceedings. (2019) - Unknown
No abstract available